The Evaluation of Exam Preparation for Reading Skills by Indonesian Daf-Teachers - Ardiyani, Dewi Kartika; RofiÃ¡h (Nusantara Science and Technology Proceedings)
The minimum competency assessment (Asesmen Kompetensi Minimum / AKM) is an assessment of the basic competencies of Indonesian learners. The AKM consists of test questions that are created by teachers. Self-competence and critical thinking of the learner are to be emphasized by these test questions. The AKM instrument comprises two basic skills, namely reading skills and mathematical skills (numeric). The aim of this study is to find out the difficulty of Indonesian German teachers in preparing for reading competence exams and to describe the AKM test questions for learning German at high school (SMA / MA) in Indonesia. This study used a descriptive-qualitative method with questionnaire as the data collection technique. The data is Indonesian German teachers (20 teachers) difficulty in reading exam preparation and the AKM test questions they had been created. Based on the data result of the questionnaire, it is found that most teachers have had difficulty creating questions about the content of the text that encourage critical thinking of the learners. In addition, the validation results of the AKM test questions show that the text selection should be adapted to the goals to be achieved. The tasks related to the text should be able to improve the productive skills of the learner, e.g. graphic form. The selected text should contain a lot of information and the answer options should not be so easy to choose. The results of this research are intended to provide information for Indonesian German teachers so that they can create AKM test questions that encourage critical thinking skills of the learners. This can then develop the learner's reading skills.